An assessment of India's multiple national social protection schemes in improving nutrition and health - Narayanan, Sudha; Naraparaju, Karthikeya; Gerber, Nicolas (Springer, 2023)
This paper examines whether the combined participation in workfare and food grain subsidy programmes in India impacts the nutritional and health status of women and children, using body mass index (BMI) and short-term morbidity as indicators. Based on a nationally representative panel data survey conducted in 2005 and 2012, we estimate the participants’ average treatment effects by applying a semi-parametric differences-in-differences (DID) approach on the full sample and a regression-based DID approach on a matched sample. We find that simultaneous participation in these programmes lowers women’s morbidity by at least 25%, but women’s BMI increases only in states implementing those programmes well. For children, there is no robust evidence of impacts. Our results suggest that various social protection programmes can operate synergistically and deliver positive impacts on children and women’s nutrition or health, even though this is not their main objective. However, the effects are heterogeneous and confirm that the nutrition and health benefits, reached through a combination of the two social protection programmes, are mediated by intrahousehold dynamics. Synergistic and mediating effects must be considered in future efforts to upscale social protection in the Global South in order to deliver simultaneous progress across the Sustainable Development Goals.